Propuesta para el tratamiento de los desechos sólidos municipales de nauta, loreto, Perú: base para proponer un plan de manejo ambiental sostenible - Pérez Vásquez, Oscar Agapito (2008)
In this investigation it was determined that the municipal solid waste generated in the city of Nauta are food processing waste, animal manure, waste of grass, paper, plastics, glass, scrap. Using the method of selecting systematic selected 189 homes, of which 20 are central layer, the stratum 169 consolidated and consolidation process. The amount total municipal solid waste that is generated is 10.5 TM/day, and the amount of organic matter is 80%. According to the results in order to reduce the volume and quantity of solid waste is proposed to develop an ecological environmental education for children, youth and the general population, so that in the future will have a sustainable management plan. Finally it is proposed to strengthen an area of treatment for developing compost and humus and the construction of a plant to produce biogas.